CUSTOMER SHOPPING DECISION IN GAJAHMADA BATANG RESTAURANT - Diva Riza Fahlefi (BISMA: Jurnal Bisnis dan Manajemen, 2021)
This study aims to determine the influence of store layout, interior display, human, and cleanliness on customer shopping orientation at Gajahmada restaurant in Kabupaten Batang. The sampling method used was accidental sampling. The data analysis method adopted in this study was multiple regression analysis. The results showed that the store layout variable has a negative and insignificant effect on the customer shopping orientation (β = -0.046 and Sig. = 0.634). Meanwhile, the interior display variable was found to positively and significantly affect the customer shopping orientation indicated by the value of β = 0.266 and Sig. = 0.003. The impact of the human variable on the customer shopping orientation also demonstrated a positive and significant impact (β = 0.346 and Sig. = 0.000). The cleanliness variable was found to positively and significantly influence customer shopping orientation (β = 0.320 and Sig. = 0.000). Furthermore, the multiple regression analysis results also indicated that all independent variables, which were store layout, interior display, human, and cleanliness, simultaneously affect the customer shopping orientation proved by the value of F= 32.929 and Sig. = 0.000. Keywords: Store layout, interior display, human variable, cleanliness, customer shopping